MILLING OF COMPLEX SURFACES - Evstati LEFTEROV; Tanya AVRAMOVA (Fiabilitate şi Durabilitate)
In the article are considered principle kinematic schemes of cutting for perform the machining of recessed and convex rotating surfaces. The mathematical dependencies determining the trajectory character described by the relative motion of the respective kinematic cutting scheme are presented. Of particular importance in performing of various principle kinematic schemes of cutting is the direction of motion of the tool relative to its rotation.